Analysis of the World Championships men's basketball (2002 and 2006). Differences between players with different levels of experience (senior and junior) - J. García; S. Ibáñez; I. Parejo; M. Cañadas; S. Feu (Asociación Española de Ciencias del Deporte, 2010)
The purpose of this study was to identify the differences between junior and senior players. Game-related statistics were used to identify the game actions that discriminated between both levels. Archival data were obtained from the FIBA website. For the analysis, senior´s games from 2002 (n=62) y 2006 (n=74) and junior´s games from 2002 (n=64) y 2006 (n=64) World Championship were used. The game-related statistics gathered included 1-, 2- and 3-points field-goals (both successful and unsuccessful), defensive and offensive rebounds, assist, fouls and turnovers The secondary variables team possession and Offensive Rating. Discriminant analysis was performed to judge which game-related statistics were more useful to discriminate between levels of competition. Men´s teams were discriminated from junior´s by their higher number of assist and 3-point successful field-goals. Junior´s teams were discriminated from senior´s by their higher number of turnovers and defensive rebounds. Key Words: game-analysis, experience, basketball, discriminant analysis